Sustainable flood management strategies for resilient cities - Okaiyeto, Samuel Ariyo; Wang, Jun; Xiao, Hongwei (International Journal of Agricultural and Biological Engineering, 2023)
The world is suffering more and more serious climate change events this summer: temperature records broken constantly, ocean waters as warm as hot tubs, floods are raging around the world. It has been confirmed that the July 2023 was the hottest month in recorded history and the average global temperature was 1.54ºC above the preindustrial average for July. The world seems to be entering the tipping points of climate change beyond which climate change will occur more dramatic and quickly, become self-perpetuating and difficult or impossible to undo. Keywords: flood disasters, management, sustainable strategies, resilient cities, global climate change, Zhuozhou cityDOI: 10.25165/j.ijabe.20231604.8584Citation: Okaiyeto S A, Wang J, Xiao H W. Sustainable flood management strategies for resilient cities. Int J Agric & Biol Eng, 2023; 16(4): 269-270.